Cross-cultural adaptation and psychometric validation of the STarT back tool for Jordanian Arabic-speaking adults with low back pain - Owis Eilayyan; Thamer A. Altaim; Alaa Salameh; Fadi M. Al Zoubi (PLoS ONE, 2025)
Background The Keele STarT Back Tool (STarTBack) was developed to categorize people with low back pain based on disability risk. The tool was cross-culturally adapted and validated in different languages and countries, including Arabic in Saudi Arabia. However, the tool has not been cross-culturally adapted and validated among Arabic-Jordanian speakers. Objective To cross-culturally adapt and validate the Keele STarT Back Tool (STarTBack) for Arabic-speaking adults with low back pain (LBP) in Jordan. Methods This prospective cross-sectional study was conducted in hospitals and physical therapy departments. The STarTBack was translated following international guidelines. Cross-cultural adaptation was assessed through interviews with experts and individuals with LBP. Internal consistency, construct validity (via correlation with related measures), and discriminative validity (using Receiver Operating Characteristic curves) were examined. Results Twenty participants participated in the content validity assessment (mean age: 41.3 years; 50% female), while 107 participants took part in the pre-final version testing (mean age: 39.2 years; 54.2% female). One item required minor modification for clarity. Our preliminary results showed that the adapted STarTBack-AR demonstrated good internal consistency (Cronbach’s α = 0.73). Moderate-to-high correlations supported construct validity. Discriminative validity was acceptable-to-excellent for disability, catastrophizing, anxiety and depression. Conclusion The culturally adapted STarTBack-AR is a reliable and valid tool for stratifying Arabic-speaking Jordanian patients with LBP according to their risk of disability. Its implementation has potential to improve care through targeted treatment approaches, thereby reducing the risk of disability.